2016
DOI: 10.2147/ijwh.s119232
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum hemorrhage: incidence, risk factors, and outcomes in a low-resource setting

Abstract: BackgroundPrimary postpartum hemorrhage (PPH) is defined as blood loss from the genital tract of 500 mL or more following a normal vaginal delivery (NVD) or 1,000 mL or more following a cesarean section within 24 hours of birth. PPH contributes significantly to maternal morbidity and mortality worldwide. Women can rapidly hemorrhage and die soon after giving birth. It can be a devastating outcome to many young families. Women giving birth in low-resource settings are at a higher risk of death than their counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
81
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 14 publications
21
81
3
5
Order By: Relevance
“…Similar results were shown by Ngwenya in a poorresource setting of Zimbabwe. 7 Sharma and Dhakal from Nepal demonstrated similar pattern as well. 8 Furthermore, we observed that deliveries who had a spontaneous onset of labor had the least blood loss.…”
Section: Discussionsupporting
confidence: 54%
“…Similar results were shown by Ngwenya in a poorresource setting of Zimbabwe. 7 Sharma and Dhakal from Nepal demonstrated similar pattern as well. 8 Furthermore, we observed that deliveries who had a spontaneous onset of labor had the least blood loss.…”
Section: Discussionsupporting
confidence: 54%
“…The mean age was 27.7 year in a study conducted by Solwayo Ngwenya on PPH: incidence risk factors and outcome at Mpilo hospital in Zimbave, for a duration from January 2016 to June 2016. 11 In this study PPH was found to be more common in 20-30 years age group. 55% of patients were between 20-30 years age group whereas A total 41% were of less than 20 years age group.…”
Section: Discussionmentioning
confidence: 49%
“…Through the study, clinical awareness and regular obstetric emergency exercises were verified through this study, which can make a difference with a reduction in the number of deaths achieving positive results and saving more lives. 17 It is confirmed that, in most of the studies selected, the maternal death caused by PPH is still alarming in the country reaching, above all, the most deprived population and representing a major public health problem. It is observed that nurses have training to act on complications in cases of PPH, although there are no protocols for interventions in this area, aiming at ensuring adequate care for the puerperium.…”
Section: Methods Objectivementioning
confidence: 78%